Cambodia and East Timor crises : revisiting and reassessing the "Asean way". - Lim, Soo Chin. (2008)
Examine the efficacy and limitations of the "ASEAN Way" as a framework for regional conflict management with respect to extramural regional and intrastate conflicts through the Cambodia and East Timor crises.